Prevention Efforts of Covid-19 Qualitative Study Transmission in East Java Province - Siti Mudrikatin (Kirana Publisher (KNPub), 2024)
East Java has seen a steady increase in COVID-19 cases, with 1,221 people affected and 3547 lives lost. The study used in-depth interviews with stakeholders supported by NGOs and the Integrated Command Post to understand the phenomenon. The sample included nine cities in East Java Province, including Surabaya, Malang, Kediri, Batu, Blitar, Madiun, Mojokerto, Pasempuan, and Probalingga. The results of these interviews were disseminated to health workers in East Java using the Question-and-Answer lecture method. The health department and stakeholders at the Integrated Command Post collaborated to socialize technical guidelines for preventing COVID-19 transmission. The material presented in the program policies aims to prevent COVID-19 transmission in East Java. Stakeholders' policies towards the Integrated Command Post capacity building program are crucial for preventing COVID-19 transmission. Regulations or laws are necessary to regulate efforts in East Java. Monitoring and evaluation are carried out by stakeholders at the integrated post in East Java, with the health department monitoring its evaluation through monthly reports sent through puskesmas and hospitals based on the COVID-19 examination laboratory network. The study aims to provide information on self-isolation and increase support and cooperation across sectors and local governments in handling COVID-19.